Nutraceutical Strategies for Enhancing Celiac Disease Management: A Review of Current Evidence - Das, Anwesha; Sharma, Hitesh Kumar; Shamim, Nilofar Jahan; Ahmed, Firuj; Singhal, Abhinav; Upadhyay, Pushkar; Grewal, Ajmer Singh; Pandita, Deepti; Lather, Viney (Current Nutrition & Food Science, 2025)
Celiac disease is an autoimmune disorder that can be triggered by the intake of a protein called gluten. Currently, a rigorous gluten-free diet is the only treatment available for celiac disease. However, recent research has shown that certain nutraceuticals may have potential in managing the symptoms of celiac disease. Nutraceuticals are food-derived products that provide health benefits beyond basic nutrition. This review investigates the functions of nutraceuticals in the management of celiac disease, including their potential for reducing inflammation, modulating the gut microbiota, and improving nutrient absorption. The potential benefits of various nutraceuticals, including probiotics, prebiotics, polyphenols, and enzymes, are discussed. Although further investigation is required to completely comprehend the effectiveness of nutraceuticals in the treatment of celiac illness, current evidence suggests that they may be a promising avenue for improving the quality of life for those with this condition. The management of celiac disease involves a multidisciplinary approach that includes diagnosis, education, and ongoing support. The key to successful management of celiac disease is early and accurate diagnosis, followed by education on the gluten-free diet and the avoidance of cross-contamination. This can be challenging, especially for those who are newly diagnosed, but with proper guidance and support, individuals with celiac disease can lead healthy and fulfilling lives. Sustained monitoring and follow-up treatment are also necessary to make sure the gluten-free diet is followed and to identify any possible issues.
Keywords: enzymes